Critical Analysis of Information Sources and Channels Preferred by Vegetable Growers of Haryana - Gondkar Sachin. S. , Chaudhary Pooja , Vister Joshi and P. S. Sherawa, (Indian Journal of Extension Education, 2015)
The present study was conducted in 2014-15 to study the rapidity, utilization and credibility pattern of information sourcesand channels by the vegetable growers in Haryana. The 160 vegetable growers from four districts of Haryana wereinterviewed. The study reported that personal localite sources like neighbours, friends, progressive and opinion farmerswere playing important role in transfer of vegetable production technologies to the vegetable growers. These sources withhigh credibility were widely used by majority of the respondents. While SMS and Scientists were perceived as most rapidsource of information for transfer of technology. The most revealing finding of the study is that ADO/BAO had lost theircredibility among the farmers while the input suppliers and agents of commercial seed, fertilizers, plant protection, etc.,played a critical role in information network of vegetable growers , however their credibility is low. It was important tonote that scientists and SMSs were perceived a much credible source of information by farmers, however these sourceswere less accessible to the farmers. Further, the increasing literacy rate and easy accessibility of the mass media channelsresulted in increased utilization of these media by the farmers.